2021
DOI: 10.3389/fneur.2021.746389
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between the Rate of Treatment Response and Short-Term Outcomes in Childhood Guillain-Barré Syndrome

Abstract: Introduction: Few studies have examined the association between the rate of treatment response and the outcome of pediatric Guillain-Barré syndrome (GBS). Therefore, our study aimed to identify treatment response in relation to the short-term outcomes of GBS. Further, we investigated its potential predictive value for prognosis.Methods: Our retrospective study included children diagnosed with GBS in the Pediatric Neurology Department of the Children's Hospital of Hebei Province from 2016 to 2020. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…The prognosis of patients with GBS is considered good; however, approximately 20% of patients are unable to walk unaided (9), and about 7% of patients died (10). As a special group, most children with GBS have a good prognosis (11,12). In this study, 29.2% (19/65) of patients at 1 month and 7.7% (5/65) of patients at 6 months had poor prognoses, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…The prognosis of patients with GBS is considered good; however, approximately 20% of patients are unable to walk unaided (9), and about 7% of patients died (10). As a special group, most children with GBS have a good prognosis (11,12). In this study, 29.2% (19/65) of patients at 1 month and 7.7% (5/65) of patients at 6 months had poor prognoses, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…The recommended dosage in adults is 0.4 g•kg -1 •d -1 for 5 consecutive days (Van den Berg et al, 2014;Liu et al, 2018;Svacǐna et al, 2019). The response rate after immunoglobulin treatment was found to correlate with clinical outcomes, and the short-term outcomes of patients that started with intravenous immunoglobulin within 1 week were significantly better than those of patients that started treatment after 1 week (Jin et al, 2021). Grattan et al (1982) reported a case of psittacosis complicated by GBS.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of GBS tends to be good after effective treatments, however, about one-fifth of the patients are unable to walk independently at 6 months after symptom onset, and about 7% of patients die ( 16 ). Many studies have shown that pediatric GBS has a good prognosis ( 17 , 18 ). In the present study, seven (7/26, 26.9%) and 19 patients (19/26, 73.1%) showed poor and good prognoses, respectively, at 1 month after symptom onset, whereas none of the patients was unable to walk independently at 6 months after symptom onset.…”
Section: Discussionmentioning
confidence: 99%